DEVELOPMENT OF EARLY CHILDHOOD TEACHER EDUCATION COMPETENCIES IN THE FIELD OF DIGITAL TECHNOLOGY IN TERNATE CITY - Radjiman Ismail (International Journal of Education, Information Technology, and Others, 2019)
This study uses a qualitative research approach. The research method uses research and development on Borg and Gall. Respondents of Early Childhood Education teacher research in the sub-district of Central Ternate city. The study aimed to improve the competence of PAUD teachers in the field of digital technology and measure the effectiveness of digital training models in developing learning materials. The use of technology in learning is still low. Mastery of technology for PAUD teachers is a necessity to help develop learning. Based on the results of the study obtained data that there is an increase in the ability of competencies to develop digital-based learning material. An effective digital training model is used to improve the competence of PAUD teachers. It is recommended that PAUD teachers always develop digital-based learning